Teicoplanin resistance in Staphylococcus haemolyticus is associated with mutations in histidine kinases VraS and WalK - Vimberg, Vladimir; Cavanagh, Jorunn Pauline; Benada, Oldřich; Kofroňová, Olga; Hjerde, Erik; Zieglerová, Leona; Balíková Novotná, Gabriela (Diagnostic microbiology and infectious disease, 2018)
We investigated the genetic basis of glycopeptide resistance in laboratory-derived strains of S. haemolyticus with emphasis on differences between vancomycin and teicoplanin. The genomes of two stable teicoplanin-resistant laboratory mutants selected on vancomycin or teicoplanin were sequenced and compared to parental S. haemolyticus strain W2/124. Only the two non-synonymous mutations, VraS Q289K and WalK V550L were identified. No other mutations or genome rearrangements were detected. Increased cell wall thickness, resistance to lysostaphin-induced lysis and adaptation of cell growth rates specifically to teicoplanin were phenotypes observed in a sequenced strain with the VraS Q289K mutation. Neither of the VraS Q289K and WalK V550L mutations was present in the genomes of 121S. haemolyticus clinical isolates. However, all but two of the teicoplanin resistant strains carried non-synonymous SNPs in vraSRTU and walKR-YycHIJ operons pointing to their importance for the glycopeptide resistance.
Keywords: genom bakteriální; Poland; Sequence Analysis, DNA; Anti-Bacterial Agents; bakteriální léková rezistence; jednonukleotidový polymorfismus; Teicoplanin; DNA, Bacterial; Drug Resistance, Bacterial; Staphylococcus haemolyticus; Staphylococcal Infections; stafylokokové infekce; fenotyp; Vancomycin; rezistence na vankomycin; Polsko; teikoplanin; DNA bakterií; Base Sequence; sekvence nukleotidů; Phenotype; Mutation; Histidine Kinase; Humans; Vancomycin Resistance; antibakteriální látky; sekvenční analýza DNA; Resistance; vankomycin; histidinkinasa; Genome, Bacterial; lidé; Polymorphism, Single Nucleotide